2017
DOI: 10.1111/jbi.13102
|View full text |Cite
|
Sign up to set email alerts
|

Elevational patterns of non‐volant small mammal species richness in Gyirong Valley, Central Himalaya: Evaluating multiple spatial and environmental drivers

Abstract: Aim Documenting the elevational species richness patterns of non‐volant small mammals and assessing the roles of pure spatial factors and spatial structured environmental factors in shaping the elevational richness patterns. Location Gyirong Valley in the Mount Qomolangma National Nature Reserve, located in the southern Himalayas, China. Methods Field surveys were conducted at each of twelve 300‐m elevational bands along a gradient from 1,800 to 5,400 m above sea level (a.s.l). For the pure spatial variables, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 82 publications
4
47
2
1
Order By: Relevance
“…Hu et al, 2014Hu et al, , 2017McCain, 2004), we found that the species richness of mammalian herbivores in QTP peaked at mid-elevations. Consistent with several previous elevational studies (e.g.…”
Section: Discussionsupporting
confidence: 46%
“…Hu et al, 2014Hu et al, , 2017McCain, 2004), we found that the species richness of mammalian herbivores in QTP peaked at mid-elevations. Consistent with several previous elevational studies (e.g.…”
Section: Discussionsupporting
confidence: 46%
“…Gyirong Valley is in a transition zone between the Oriental and Palearctic realms (Hu et al, ; Zhang, ), characterized by complicated geological structure, varied geomorphologic types, rich biodiversity, and variable mountain climate. There are five climate types in the Valley: (a) the Mountainous Subtropical Zone, (b) the Mountainous Warm Temperate Zone, (c) the Mountainous Cold Temperate Zone, (d) the Subalpine Frigid Zone, and (e) the Alpine Frigid Zone (Hu et al, ). The wet season approximately lasts from May to October, whereas the dry season is from November to April.…”
Section: Methodsmentioning
confidence: 99%
“…Plant species richness represented structural complexity of the habitat (Hu, et al, ). To acquire plant community data in Gyirong Valley, field surveys of plants were conducted in three 20 × 20 m‐quadrats in each 300‐m elevational band.…”
Section: Methodsmentioning
confidence: 99%
“…It is not surprising that the energy hypothesis is supported in our data, as a positive relationship between diversity and productivity of small mammals was frequently reported by previous studies (Chen et al, ; McCain et al, ). MDE has generated considerable controversy because of the high variable explanatory power (McCain, ), even in studies on small mammals (Hu et al, ; Rowe, ; Wu, Yang, et al, ). A possible reason for the high fit of MDE in our study is the vast extent of our study area (2600–4200 m), which makes a high degree of overlap in the central area.…”
Section: Discussionmentioning
confidence: 99%